The impacts of forestry decentralization on district finances, local communities and spatial planning: a case study in Bulungan District, East Kalimantan - Samsu; Suramenggala, I.; Komarudin, Heru; Ngau, Y. (Center for International Forestry Research, 2005)
The report describes the impacts of forestry decentralization on district finance, local communities and spatial planning, drawing on an 18-month research project in Bulungan District in East Kalimantan Province. It describes forestry management policies following the implementation of regional autonomy, and their impacts on district revenue and local livelihoods. The authors analyze district spatial planning, forest land use and community control over forest lands. While agreeing that decentralized forest policies have had positive impacts in Bulungan District, the report highlighted a number of issues that both district and central governments and stakeholders need to examine if the decentralization of the forestry sector is to be successful. These issues include the lack of coherent policies and coordination between central and district governments; lack of adequate resources on the part of both district and central governments to manage, monitor and control the use of the forest resource; weak district tax collection mechanisms and ineffective imposition of penalties, and the failure of the decentralized policies to ensure that the local people benefit from the resource.